What is resistant arterial hypertension? - Evgeniya V. Shalaeva; Franz H. Messerli (Blood Pressure, 2023)
Purpose The current review is to describe the definition and prevalence of resistant arterial hypertension (RAH), the difference between refractory hypertension, patient characteristics and major risk factors for RAH, how RAH is diagnosed, prognosis and outcomes for patients. Materials and Methods According to the WHO, approximately 1.28 billion adults aged 30–79 worldwide have arterial hypertension, and over 80% of them do not have blood pressure (BP) under control. RAH is defined as above-goal elevated BP despite the concurrent use of 3 or more classes of antihypertensive drugs, commonly including a long-acting calcium channel blocker, an inhibitor of the renin-angiotensin system (angiotensin-converting enzyme inhibitor or angiotensin receptor blocker), and a thiazide diuretic administered at maximum or maximally tolerated doses and at appropriate dosing frequency. RAH occurs in nearly 1 of 6 hypertensive patients. It often remains unrecognised mainly because patients are not prescribed ≥3 drugs at maximal doses despite uncontrolled BP. Conclusion RAH distinctly increases the risk of developing coronary artery disease, heart failure, stroke and chronic kidney disease and confers higher rates of major adverse cardiovascular events as well as increased all-cause mortality. Timely diagnosis and treatment of RAH may mitigate the associated risks and improve short and long-term prognosis.